2011
DOI: 10.1016/j.cell.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Human Exonuclease 1 DNA Complexes Suggest a Unified Mechanism for Nuclease Family

Abstract: Summary Human exonuclease 1 (hExo1) plays important roles in DNA repair and recombination processes that maintain genomic integrity. It is a member of the 5′ structure-specific nuclease family of exonucleases and endonucleases that includes FEN-1, XPG, and GEN1. We present structures of hExo1 in complex with a DNA substrate, followed by mutagenesis studies, and propose a common mechanism by which this nuclease family recognizes and processes diverse DNA structures. hExo1 induces a sharp bend in the DNA at nick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
285
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(302 citation statements)
references
References 69 publications
14
285
2
Order By: Relevance
“…As expected, nuclease-dead Exo1(D78A/D173A) bound at the 3′-ssDNA ends but did not move on DNA (mean velocity = 0.1 ± 0.5 bp/s; processivity = 0.01 ± 0.3 kb, n = 19; Fig. 1E) (32). We also did not observe any resection when EDTA was substituted for divalent metal ions (Fig.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…As expected, nuclease-dead Exo1(D78A/D173A) bound at the 3′-ssDNA ends but did not move on DNA (mean velocity = 0.1 ± 0.5 bp/s; processivity = 0.01 ± 0.3 kb, n = 19; Fig. 1E) (32). We also did not observe any resection when EDTA was substituted for divalent metal ions (Fig.…”
Section: Resultssupporting
confidence: 48%
“…Stationary hExo1 may stem from protein inactivation during overexpression and purification or may be an intrinsic property of the enzyme. In support of the second model, a recent X-ray crystallographic study of hExo1 suggested that the largely unstructured C terminus, which is present in our full-length protein, harbors an auto-inhibitory domain (32). This domain interacts with hMSH2 and hMLH1 (40,41) and is critical for hMutSα stimulation of hExo1 nuclease activity (5,32,42).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Analysis of the structures of FEN1 (Tsutakawa et al 2011) and EXO1 (Orans et al 2011), which were solved at similar times, suggest a unified mechanism for this type of nuclease involving DNA bending and two nucleotide 'fraying' of one strand (Orans et al 2011).…”
Section: Fen1mentioning
confidence: 92%
“…The Mlh1-Pms1/ Pms2 complex has an endonuclease activity suggested to play a role in the initiation of the excision step of MMR (24,25). Downstream of mismatch recognition is a mispair excision step that can be catalyzed by Exonuclease 1 (Exo1) (26)(27)(28); however, defects in both S. cerevisiae and mouse Exo1 result in only a partial MMR deficiency, suggesting the existence of additional excision mechanisms (26,27,29). DNA polymerase δ, the singlestrand DNA binding protein replication protein A (RPA), the sliding clamp proliferating cell nuclear antigen (PCNA), and the clamp loader replication factor C (RFC) are also required for MMR at different steps, including activation of Mlh1-Pms1/Pms2, stimulation of Exo1, potentially in Exo1-independent mispair excision, and in the gap-filling resynthesis steps of MMR (3,16,17,24,27,(30)(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%